GPU implementation of linear morphological openings with arbitrary angle - Karas, Pavel; Matula, Petr (Journal of real-time image processing, 2015)
Linear morphological openings and closings are important non-linear operators from mathematical morphology. In practical applications, many different orientations of digital line segments must typically be considered. In this paper, we (1) review efficient sequential as well as parallel algorithms for the computation of linear openings and closings; (2) compare the performance of CPU implementations of four state-of-the-art algorithms; (3) describe GPU implementations of two recent efficient algorithms allowing arbitrary orientation of the line segments; (4) propose, as the main contribution, an efficient and optimized GPU implementation of linear openings; and (5) compare the performance of all implementations on real images from various applications. From our experimental results, it turned out that the proposed GPU implementation is suitable for applications with large, industrial images, running under severe timing constraints.